Polskie duchowieństwo rzymskokatolickie wobec cesarza Napoleona i wydarzeń 1812 roku = The Polish Roman Catholic clergy in relation with the emperor Napoleon and the events in 1812 - Góralczyk, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The events which took place within the Polish borders in 1812 captured the attention of the Polish Roman Catholic clergy. The atmosphere of those days resembled the one in 1807. The priests inspired from their pulpits the hope for an improvement in the situation of the Church. The Emperor Napoleon was gaining the favor of the crowds. Despite the fact of imprisonment of Pius VII, which only caused the clergy to remain silent, the French ruler was still called by the priests Napoleon the Great and treated as the authentic God?s messenger. The clergy greeted the Emperor?s attendants within the territory of the Grand Duchy of Warsaw by tolling in the church bells.
Keywords: Napoleon I (cesarz Francuzów; 1769-1821); kościół katolicki; wojny napoleońskie - 1803-1815